An empirical analysis of brand image of Sitakunda as a tourist destination - Masum, Md. Yeamin; Khairuzzaman , Khairuzzaman; Tanvir, Mehedi Hasan; Hasan , Md. Sakib (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: The study aims to establish a powerful brand image and create an emotional bond between tourists and destinations. Based on visitors' opinions of various aspects of tourism, this study seeks to create a powerful brand image of Sitakunda as a travel destination. Research Methodology: The study gathered 312 samples using a quantitative survey to examine people's opinions about Sitakunda as a tourism destination.  Descriptive statistics and reliability analysis techniques were used to discuss the methodology section of this study. Results: The study found that tourism significantly contributes to establishing Sitakunda's brand image as a tourist destination. Conclusion: The study concludes that establishing a strong brand image centered on Sitakunda’s distinctive quality-price ratio is essential for enhancing its global recognition and tourism appeal. Limitations: The sample for the research is limited to the people living in Sitakunda and tourists from different areas of Bangladesh. Contribution: The paper's empirical insights offer information on the actual experiences and results of the brand image of Sitakunda as a tourist destination. Practical Implications: The research recommends that social media marketing is essential for promoting any destination as a brand. Finally, the study urges stakeholders to work proactively to establish a powerful brand image for any tourist location.